ASSESSMENT OF THE MAXIMUM TSUNAMI WAVE HEIGHTS ON THE CRIMEA-CAUCASUS COAST OF THE BLACK SEA FROM POSSIBLE UNDERWATER EARTHQUAKES AND LANDSLIDES IN THE DZHUBGA AREA - R.Kh. Mazova,; A.A. Suchkov; A.A. Kurkin (Science of Tsunami Hazards, 2023)
In the present work, the problem of tsunami wave generation is solved by considering two source mechanisms: a seismic source and a landslide source. The numerical simulation was performed with the localization of the source in the Dzhubga area, where the Blue Stream pipeline comes ashore. For both problem statements, different source localizations were considered: at depths of 350 m and 750 m. For the seismic setting, a two-block source with any directional movement of blocks was considered. The landslide problem was considered within the framework of a solid-block segmental model. Numerical simulation of the generation of the tsunami source and the propagation of tsunami waves over the Black Sea from Sochi to the Crimea peninsula has been performed. Landslide danger sections of the Turkish Stream and Blue Stream pipelines were examined in the most detailed way. For each scenario, the characteristics of wave fields in the computation water area were obtaine